Councils, Managers. . . and Consultants? Management Consulting and Complementarity in Municipal Strategy Implementation. Issue 1 (January 2023) - Mitchell, David
American governments spend $6 billion annually on management consulting, with steady growth. However, public-sector consulting receives little scholarly and public attention—especially for local governments. For which municipal projects are management consultants best suited? Svara asserts that complementarity promotes effective governance between city councils and their managers; sometimes, however, neither has the capability to lead the other. This study explores whether consultants can effectively fill this complementarity void by examining 205 strategic initiatives from 43 US municipalities. The analysis confirms that consultants are helpful when strategic and political-administrative contexts conflict, but only when key stakeholders are supportive.